2012
DOI: 10.1590/s1516-31802012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Citation distribution profile in Brazilian journals of general medicine

Abstract: CONTEXT AND OBJECTIVE: Impact factors are currently the bibliometric index most used for evaluating scientific journals. However, the way in which they are used, for instance concerning the study or journal types analyzed, can markedly interfere with estimate reliability. This study aimed to analyze the citation distribution pattern in three Observou-se que a distribuição das citações a esses artigos é altamente enviesada, com um grande número de trabalhos pouco citados e um pequeno percentual com muitas citaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…the percentage of citable items receiving less citations than indicated by the JIF, the present study obtained about 65% of CI for all three journal cohorts (corresponding to about 35% CI receiving more citation than the mean)-similar to previously reported values (Asaad et al 2019;Larivière et al 2016;Larivière and Sugimoto 2019). A symmetric distribution would result in about 50% CI below/above the mean (JIF) thus demonstrating the JIF to overestimate the real 'average' citation rate in virtually (a)…in case of individual journals, the journal title is given by the JCR abbreviation; (b)…estimated from the diagrams in (Opthof and Coronel 2002) and (Lustosa et al 2012); (c)…mean values for the three journals; (d)…for 2005; (e)…n = 30 randomly chosen papers per journal per year. (f)…for original articles/reviews, respectively; (g)… the 11 journals selected are both, multidisciplinary and subject-specific, have a JIF in the range between 3 to > 30, and are published by seven different publishers (Larivière et al 2016); (h)…the top 3 journals in the cohort of plastic surgery journals (Asaad et al 2019 all journals.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…the percentage of citable items receiving less citations than indicated by the JIF, the present study obtained about 65% of CI for all three journal cohorts (corresponding to about 35% CI receiving more citation than the mean)-similar to previously reported values (Asaad et al 2019;Larivière et al 2016;Larivière and Sugimoto 2019). A symmetric distribution would result in about 50% CI below/above the mean (JIF) thus demonstrating the JIF to overestimate the real 'average' citation rate in virtually (a)…in case of individual journals, the journal title is given by the JCR abbreviation; (b)…estimated from the diagrams in (Opthof and Coronel 2002) and (Lustosa et al 2012); (c)…mean values for the three journals; (d)…for 2005; (e)…n = 30 randomly chosen papers per journal per year. (f)…for original articles/reviews, respectively; (g)… the 11 journals selected are both, multidisciplinary and subject-specific, have a JIF in the range between 3 to > 30, and are published by seven different publishers (Larivière et al 2016); (h)…the top 3 journals in the cohort of plastic surgery journals (Asaad et al 2019 all journals.…”
Section: Discussionsupporting
confidence: 80%
“…that the relatively high JIF of the Top 3 journals within each category tends to attract citations to all published items in these journals thus reducing the proportion of non-cited articles. As shown in Table 3, other studies reported values in the range between < 20 and 70% of CI (Weale et al 2004;Asaad et al 2019;Opthof et al 2004;Lustosa et al 2012;Bozzo et al 2017). Weale and colleagues (Weale et al 2004) discussed the percentage of articles per journal receiving no citations (rate of non-citation) as a possible alternative for measuring journal quality due to their observation that high-JIF journal have lower rates of non-citations.…”
Section: Discussionmentioning
confidence: 86%
“…constatou-se um aumento na média de autores externos citados por redação e verificou-se uma mudança na moda de 0 para 1 autor externo citado por redação. trabalhos que fluem nesse sentido em diferentes áreas são os estudos de marketing de Vieira (2003), de psicologia de Sampaio (2008), de empreendedorismo de Borba, Hoeltgebaum e Silveira (2011) e de medicina de Lustosa et al (2012).…”
unclassified